Back Cover: A Full Topological Analysis of Unstable and Metastable Bond Critical Points (ChemPhysChem 1/2015). Issue 1 (12th January 2015) - Miorelli, Jonathan; Wilson, Tim; Morgenstern, Amanda; Jones, Travis; Eberhart, Mark E.
<x xml:space="preserve">Abstract</x> The cover picture shows He in an adamantane cage. The gradient field (blue) about the CHe bond path is unusual compared to the gradient field (red) about a CC bond path. The figure was produced from charge density generated by an applied density functional by using Tecplot's Bondalyzer package, as described by M. E. Eberhart et al. on p. 152.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>